2018
DOI: 10.1021/acs.chemrev.7b00733
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Interference, Graphs, Walks, and Polynomials

Abstract: In this paper we explore quantum interference in molecular conductance from the point of view of graph theory and walks on lattices. By virtue of the Cayley-Hamilton theorem for characteristic polynomials and the Coulson-Rushbrooke pairing theorem for alternant hydrocarbons, it is possible to derive a finite series expansion of the Green's function for electron transmission in terms of the odd powers of the vertex adjacency matrix orHückel matrix. This means that only odd-length walks on a molecular graph cont… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 143 publications
(341 reference statements)
3
62
0
5
Order By: Relevance
“…Tsuji and Hoffmann [27] have shown and discussed with great clarity that in conduction calculations based on the HMO model Hamiltonian, QI can be predicted for a pair of atoms µ and ν using the zeroth-order Green's function…”
Section: Quantum Interference Via Linear Superposition Of Many-bodmentioning
confidence: 99%
See 1 more Smart Citation
“…Tsuji and Hoffmann [27] have shown and discussed with great clarity that in conduction calculations based on the HMO model Hamiltonian, QI can be predicted for a pair of atoms µ and ν using the zeroth-order Green's function…”
Section: Quantum Interference Via Linear Superposition Of Many-bodmentioning
confidence: 99%
“…From a theoretical stand point, a number of studies have established qualitative relationships between observed/predicted QI trends with conjugation patterns in hydrocarbons-destructive QI in cross-conjugated molecules and constructive QI in linearly conjugated ones [26][27][28]. In particular, Markussen et al have presented a set of graphical rules to predict if a molecular structure can lead to QI or not [24].…”
Section: Introductionmentioning
confidence: 99%
“…Простейший подход к GF основывается на схемах TB, которые использовались еще в начале зарождения SME [59]. Но поразительно, что модели TB и поныне продолжают довольно часто применяться в SME, и недавно вышел интересный обзор Хоффмана [11] и сотр. по чисто хюккелевской теории молекулярной проводимости.…”
Section: электропроводность сопряженной молекулыunclassified
“…В данном обзоре этот термин означает записанный выше специальный случай (1), когда элемент симметрии антикоммутирует с базисным оператором, отражающим, возможно, и приближенно, некие фундаментальные свойства молекулы. Стоит отметить, что хотя ряд симметрийных аспектов близких задач был истолкован еще в статье Макинтоша [7], квантовохический контекст требует иных акцентов и дальнейших обобщений, в част-https://doi.org/10.26565/2220-637X-2019-32-01 ности в свете современных проблем теории электрической проводимости органических молекул [8][9][10][11][12]. Наше изложение, объединяющее различные задачи, включает и новые результаты, но больше опирается на прежние и совсем недавние работы, изложенные теперь в едином ключе.…”
Section: Introductionunclassified
“…Exploiting QI for practical purposes requires that decoherence effects are minimal; it is an experimentally established fact that with increase in temperature, destructive interference effects are lost resulting in enhanced conductivity [23]. ones [26][27][28]. In particular, Markussen et al have presented a set of graphical rules to predict if a molecular structure can lead to QI or not [24].…”
Section: Introductionmentioning
confidence: 99%